Advanced materials for plasma facing components in fusion devices - Thomas, G; Gareth James Thomas (2009)
This thesis describes the design, manufacture and characterisation of thick vacuum plasma sprayed tungsten (W) coatings on steel substrates. Fusion is a potentially clean, sustainable, energy source in which nuclear energy is generated via the release of internal energy from nuclei. In order to fuse nuclei the Coulomb barrier must be breached - requiring extreme temperatures or pressures – akin to creating a ‘star in a box’. Tungsten is a promising candidate material for future fusion reactors due to a high sputtering threshold and melting temperature. However, the large coefficient of thermal expansion mismatch with reactor structural steels such as the low activation steel Eurofer’97 is a major manufacturing and in-service problem. A vacuum plasma spraying approach for the manufacture of tungsten and tungsten/steel graded coatings has been developed successfully. The use of graded coatings and highly textured 3D interface surfi-sculpt substrates has been investigated to allow the deposition of thick plasma sprayed tungsten coatings on steel substrates. Finite element models have been developed to understand the residual stresses that develop in W/steel systems and made use of experimental measurements of coating thermal history during manufacture and elastic moduli measured by nano-indentation. For both the graded and surfi-sculpt coating, the models have been used to understand the mechanism of residual stress redistribution and relief in comparison with simple W on steel coatings, particularly by consideration of stored strain energy. In the case of surfi-sculpt W coatings, the patterned substrate gave rise to regular stress concentrating features, and allowed 2mm thick W coatings to be produced reproducibly without delamination. Preliminary through thickness residual stress measurements were compared to model predictions and provided tentative evidence of significant W coating stress relief by regulated coating segmentation.